2019
DOI: 10.18203/issn.2454-5929.ijohns20195698
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic use of antibiotics as per SIGN 104 guidelines versus routine antibiotic prophylaxis for prevention of surgical site infection in clean and clean contaminated ENT surgical procedures: a comparative study

Abstract: <p class="abstract"><strong>Background:</strong> Many clinicians continue to use antibiotic prophylaxis routinely in all surgical procedures, ignoring the guidelines issued by policy makers. In this prospective study we compared the rate of surgical site infection (SSI) in patients who received prophylactic antibiotics as a routine; with the rate of SSI in patients getting antibiotics strictly as per SIGN 104 Guidelines, for clean and clean contaminated procedures.</p><p class="abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…2 However, it has been noted that prolonged antibiotic prophylaxis does not decrease surgical infection and is associated with higher levels of bacterial resistance. 3 Although, we have effective guidelines proposed for prophylaxis and treatment of SSIs, a constant threat by emerging MDR organisms is alarming. Evidence showed that MRSA and MR-CNS strains isolated from surgical wounds showed multi-drug resistance towards ampicillin, cotrimoxazole, erythromycin, clindamycin, ciprofloxacin, cefotaxime and ceftazidime.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, it has been noted that prolonged antibiotic prophylaxis does not decrease surgical infection and is associated with higher levels of bacterial resistance. 3 Although, we have effective guidelines proposed for prophylaxis and treatment of SSIs, a constant threat by emerging MDR organisms is alarming. Evidence showed that MRSA and MR-CNS strains isolated from surgical wounds showed multi-drug resistance towards ampicillin, cotrimoxazole, erythromycin, clindamycin, ciprofloxacin, cefotaxime and ceftazidime.…”
Section: Introductionmentioning
confidence: 99%